Deforestation Trends in the Congo Basin : Transport - Megevand, Carole; Dulal, Hari; Braune, Loic; Wekhamp, Johanna (World Bank, Washington, DC, 2014)
The Congo Basin is among the most poorly served areas in terms of transport infrastructure in the world, and it faces a challenging environment with dense tropical forests crisscrossed by numerous rivers that require construction of numerous bridges. Given such complexities, constructing transport infrastructure as well as properly maintaining it is certainly a key challenge for the Congo Basin countries. Recent studies indicate that investment required per kilometer of new roads is substantially higher than in other regions of Sub-Saharan Africa (SSA) and the same applies for maintenance. The physical capital of transport infrastructure is deteriorated in the Congo Basin. The ratio of classify roads in good and fair conditions range from 25 percent in Republic of Congo to 68 percent in the Central African Republic, which is globally lower than the average for low-income countries (LICs) and resource-rich countries. Other transportation assets (railways and river system) are also limited: the railway network is essentially a legacy of the colonial era and mainly used for mineral transportation, while the river system is basically only marginal.